Retrospektivni biomonitoring onesnaženosti ekosistemov Šaleške doline s svincem in fluoridi z uporabo rogovja srnjakov - Pokorny, Boštjan (Zbornik gozdarstva in lesarstva, 2006)
Contents of lead and fluorides were determined in the historical set of 129 roe deer antlers, shot in the period 1961-2004 in the vicinity of the Šoštanj Thermal Power Plant (ŠTPP), the Šalek Valley, Slovenia. The highest levels of both pollutants were determined in antlers from the sixties/eighties (Pb: ? = 4.21 } 2.57 mg/kg, max = 7.28 mg/kg; F-: ? = 1453 } 113 mg/kg, max = 2590 mg/kg), while the lowest levels were found in the most recent antlers (2000-2004 period: Pb: ? = 0.58 } 0.11 mg/kg, min = 0.15 mg/kg; F-: ? = 500 } 113 mg/kg, min = 110 mg/kg). Pollution with inorganic substances has continuously decreased in the study area during the last decades, which confi rms the effi ciency of some ecological remediation measures carried out in theŠalek Valley (e.g. construction of the remote heating system, introduction of unleaded petrol, and particularly construction of the flue gas cleaning devices at the ŠTPP, respectively). Indeed, highly positive correlations between annual emissions of gaseous pollutants from the ŠTPP and the mean yearly Pb/F- levels in roe deer antlers indicate that the decrease of Pb/F- contents in antlers reflects a significant reduction of emissions from the ŠTPP; consequently, it confirms the effectiveness of remediation measures implemented on/at the ŠTPP itself.
Keywords: biomonitoring; fluoridi; onesnaženost okolja; rogovje; srnjad; Šalek Valley; Šaleška dolina; Termoelektrarna Šoštanj